Turn kinetics during snowboard carving - Feeney, D.; Vladika, B.; Harrison, K. (Footwear Science, 2021)
Snwboarding turns on grooned terrain are called carving. Carving requires riders to increase force quickly onto the toe or heel edge of their snowboard. There is little scientific literature characterising the forces during heel and toe tums outside of work on jump landings (Krüger & Edelmann-Nusser, 2009), nor any research on the effect of different fits of boots on riding.